Objective and subjective visual quality after implantation of all optic zone diffractive multifocal intraocular lenses: a prospective, case-control observational study. Issue 11 (22nd February 2016) - Chen, Tianyu; Yu, Fang; Lin, Huayou; Zhao, Yinying; Chang, Pingjun; Lin, Lei; Chen, Qi; Zheng, Qian; Zhao, Yun-e; Lu, Fan; Li, Jin
Abstract : Background and aims: To evaluate the objective and subjective optical quality of all optic zone diffractive multifocal intraocular lens (IOL). Methods: Fifty patients (50 eyes) having phacoemulsification and IOL implantation surgery were enrolled. 25 patients were implanted with all optic zone diffractive multifocal IOL and 25 patients with monofocal IOL. Objective optical quality parameters under 4 mm pupil using Optical Quality Analysis System (OQAS), subjective visual acuity (VA) at 85 cd/m 2 luminance and questionnaire concerning halo and visual function were assessed. Results: The multifocal group gained similar objective optical outcomes, such as OQAS values at contrast 100%, 20%, 9%, modulation transfer function cut-off and Strehl ratio, as the monofocal group. Objective scatter index (OSI) was significantly better in the monofocal group. Distance corrected near VA, uncorrected near VA, distance corrected intermediate VA and uncorrected intermediate VA were significantly better in the multifocal group. The difference in uncorrected distance VA and best corrected distance VA between the monofocal and multifocal groups was not significant. Mild halos and glare were reported in both groups and a significant difference between the two groups was not observed; however, moderate glare and halos were reported only in the multifocal group (2/25). There was no significant difference between the two groups when visual function was compared. Conclusions: All optic zone diffractive multifocal IOLs provided almost the same objective optical quality as monofocal IOLs did under 4 mm pupil besides good all distance visual performance, but with greater OSI, indicating that implantation provides good optical quality in daytime but with more intraocular scatter light. Trial registration number: NCT02234635, post-results.